cpp11armadillo: An R package to use the Armadillo C++ library - Mauricio Vargas Sepulveda; Jonathan Schneider Malamud (SoftwareX)
This article introduces ‘cpp11armadillo’, an R package that integrates the highly efficient Armadillo C++ linear algebra library with R through the ‘cpp11’ interface. Designed to offer significant performance improvements for computationally intensive tasks, ‘cpp11armadillo’ simplifies the process of integrating C++ code into R. This package is particularly suited for R users requiring efficient matrix operations, especially in cases where vectorization is not possible. Our benchmarks demonstrate substantial speed gains over native R functions and Rcpp-based setups.